2010
DOI: 10.1007/s00405-010-1463-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating cerebellar and brainstem lesions with ocular vestibular-evoked myogenic potential test

Abstract: This study applied both ocular vestibular-evoked myogenic potential (oVEMP) and cervical VEMP (cVEMP) tests in patients with cerebellar disorders to determine whether VEMP test can differentiate between cerebellar and brainstem lesions. A total of 12 patients with cerebellar disorder, including extended cerebellar lesion (involving the brainstem) in 8 and localized cerebellar lesion (excluding the brainstem) in 4, were enrolled in this study. All patients underwent caloric, visual suppression, and oVEMP and cV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Cerebellar lesions affecting the brainstem, however, revealed abnormal oVEMP and cVEMP responses in 88 and 75%, respectively (Su and Young, 2011). It was only the rate of abnormal oVEMPs which significantly differed between the two groups, indicating that oVEMPs may help to differentiate between cerebellar and brainstem lesions.…”
Section: Central Vestibular Disordersmentioning
confidence: 93%
“…Cerebellar lesions affecting the brainstem, however, revealed abnormal oVEMP and cVEMP responses in 88 and 75%, respectively (Su and Young, 2011). It was only the rate of abnormal oVEMPs which significantly differed between the two groups, indicating that oVEMPs may help to differentiate between cerebellar and brainstem lesions.…”
Section: Central Vestibular Disordersmentioning
confidence: 93%
“…Lesions of the nodulus or uvula may affect the otolith-ocular reflexes and oVEMPs [30]. A study found absent oVEMPs in patients with cerebellar lesions extending into the brainstem, but normal responses in patients with isolated cerebellar lesions [39]. Abnormal VEMPs in isolated cerebellar lesions suggest a 'modulatory role' of the cerebellum on the otolithic function, or some cases of technically abnormal VEMPs, or perhaps the lesions larger than they appear on imaging.…”
Section: Cerebellar Representationmentioning
confidence: 97%
“…Reports about cVEMPs in central nervous system lesions are scarce, and our experience is dominated by peripheral vestibular system disorders such as Ménière's disease, vestibular neuritis, superior semicircular canal dehiscence, and other inner ear perilymphatic fistulas (6). Our experience in patients with cerebellar lesions is evolving, with only a few cases published (7,8), and more illustrative cases are required. Other studies involving lesions in the posterior fossa have focused on the brainstem either alone or together with the cerebellum (9Y15).…”
mentioning
confidence: 87%